The Impact of Workload on Faculty Performance: Implications for Policy Revision. A Study of a Private Medical College in Saudi Arabia - Sibai, Mohamad Tarif; Alabdullaziz , Fatma; Al-Matouq, Jenan Ahmed (Advances in Social Sciences Research Journal, 2023)
This study sought to determine the impact of workload on faculty performance, specifically on teaching and instructional performance, the performance of administrative and professional responsibilities, community service, research, and appraisal at one of the medical private colleges in Saudi Arabia. In addition, the profile of the respondents was described based on faculty workload and faculty performance. The results of this study may serve as the basis for college authorities to determine the effective and efficient faculty workload and how to properly allocate time for the other major trifocal functions in education, community service, and research production. This study utilized a cross-sectional research design with quantitative data collected from 102 faculty members. Based on the results, an increased faculty workload yields higher performance in community service and appraisal, while an increased teaching position and teaching experience increase performance in research and appraisal. A higher teaching experience is linked to increased performance in administrative and professional responsibilities, community service, research, and appraisal. On the other hand, there is no link between faculty workload, teaching position, teaching experience to teaching and instructional performance.